PEMBUATAN ASAP CAIR TANDAN KOSONG KELAPA SAWIT UNTUK PENGAWET DAN FLAVOURING IKAN PINDANG KEMBUNG (Rastrelliger sp.) - Lina Widawati; Budiyanto Budiyanto (Faculty of Agricultural Technology, University of Jember, 2014)
Solid waste from oil palm factory such as oil palm fruit bunches can polute environment it if doesn’t get an appropriate treatment. This research tried to investigate the use of oil palm fruit bunches for liquid smoke that is used in making boiled salted Kembung (Rastrelliger sp.) fish. The objective of this research is to find the effect of liquid smoke from oil palm fruit bunches on boiled salted kembung fish and also to evaluate the result from microbiologist and organoleptic of view. And also to investigate the economic value liquid smoke from oil palm fruit bunches when it is used for making liquid smoke. Boiled salted kembung fish was dyeing in liquid smoke 1%, 2%, and 3%, then do analyze Total Plate Count and organoleptic during storage on 0, 3, 5, and 7 days at room temperature. The result shows that boiled salted kembung fish on a microbiologically test as a control treatment only stand until the third day of storage, mean while with the application of liquid smoke 1%, 2%, and 3% the boiled salted kembung can stand until the seventh day of storage. From the organoleptic point of view, the panelists are prefer to consume the kembung fish with liquid smoke process. From the economic value, process of liquid smoke from oil palm fruit bunches is more potential than conventional process of oil palm fruit bunches.Keywords: liquid smoke, oil palm fruit bunches, boiled salted kembung fish, total plate count, organoleptic